Etika Bisnis Islam dalam Pemikiran Yusuf Al Qardhawi - Rizky Maudy Anggraini; Siti Latifah; Syarifuddin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Business ethics is crucial to be addressed in the era of globalization, which often neglects moral and ethical values. Therefore, Islam emphasizes that business activities should not merely aim to satisfy desires but should also strive to achieve a balanced life with positive and non-destructive behavior. Yusuf al-Qaradâwi views that modern business significantly contributes to solving ethical issues comprehensively. His moderate perspective reflects that the business ethics he proposed is a form of professionalism that will ensure business sustainability. Conducting business ethically means running a profitable venture in accordance with Islamic law. This research is a type of library research, where data collection techniques are carried out through literature studies from books, theories, journals, and other information relevant to the research problem and objectives. The results of this study are expected to enhance understanding of Islamic business ethics and provide deeper insights into its relevance to the thoughts of Yusuf al-Qaradawi. The practical implications of this research provide guidance for business practitioners, academics, and policymakers in integrating business ethics that align with Islamic values into modern business practices.